Spontaneous Resolution Induced by a Chiral Ni(II) Complex with an Achiral Tripodal Ligand#. (18th February 2015) - Sarkar, Shuranjan; Moon, Dohyun; Kim, Seog K.; Lah, Myoung Soo; Lee, Hong‐In
<x xml:space="preserve">Abstract</x> A chiral nickel(II) complex, [Ni(II)H3L](ClO4)2 (1), with an achiral ligand H3L (=tris{2‐(4‐imidazolyl)methyliminoethyl}amine) was synthesized by in situ reaction between nickel(II) perchlorate hexahydrate and a condensation mixture of 4‐imidazolecarboxaldehyde and tris(2‐aminoethyl)amine. Single crystal X‐ray analysis revealed that the H3L ligand hexadentately binds to Ni(II) ion through three Schiff‐base imine N atoms and three imidazole N atoms with distorted octahedral geometry. Both single‐crystal X‐ray diffraction and circular dichroism investigations found that the crystal of complex 1 was an enantiopure conglomerate. The hydrogen‐bond network of NimidazoleH⋯OClO4⋯HNimidazole induced spontaneous resolution to form the conglomerate. The capped tripod‐shaped [Ni(II)H3L]2+ complex ions are hydrogen‐bonded in a tail‐to‐tail mode and array in an up‐and‐down manner repeatedly to honeycomb an extended two‐dimensional homochiral network with trigonal voids.